Novel genetic variation associated to CSN3 strongly affects rennet-induced milk coagulation. (August 2017) - Poulsen, Nina A.; Gregersen, Vivi R.; Maciel, Guilherme M.; Madsen, Lone B.; Buitenhuis, Bart; Hansen, Mikka S.; Bendixen, Christian; Larsen, Lotte B.
Abstract: The effect on rennet-induced milk coagulation of three novel genetic haplotypes in close proximity to CSN3 encoding κ-casein was evaluated. Milk samples were collected from 71 Danish Holstein cows homozygous for the three novel haplotypes named according to which genetic variants of CSN3 they were characterised by: AE, A and B, respectively. The results documented that haplotype AE had significantly longer rennet coagulation time and lower curd firming rate compared with haplotypes A and B. Haplotype AE milk was further characterised by larger casein micelles and lower relative content of κ-casein, whereas the total protein contents did not differ among haplotypes. These findings indicate that the genetic κ-casein A variant can be divided into two groups with poor and good milk coagulation properties. Furthermore, three milk samples were identified as non-coagulating. These were all associated with the haplotype AE.